Aquatic Productivity Analysis based on The Relationship between Physical and Chemical of Benthic Sediment with NO3 and PO4 in the Estuarine of Tuntang River - Djoko Suprapto; Pujiono W. Purnomo; Bambang Sulardiono (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2014)
There are several types of water mixing in the estuary, as anexample is tuntang river which could be a model in the coast of northjava island.The aims of this research are known, the spatial distribution of physical structure, organic matter, including he content ofNitrogene and phosphor in the sediment. Further more the role of physical and chemical sediment are also evaluated. The researchwas conducted in of May 2014, in an area which devided into 11 stations : one of them is located before the esturary while in thewest, north west, east and north east the station are distributed proportionally. The variables measured are total organic matters,total nitrogen, total phosphate, NO3-N, PO4-P , Dissolved oxygen, current, depth and visibility. The result of the research shown thatspatial distribution of the sediment strongly suggest the form of clay in front of estuary, south westward as well as north westwards.Clay distribution is well influenced by organic matter and nitrogene while phosphate content tend to be randomly distributed. In thecase of the the current is weak while the oxygen content is high enough so that the relationship between nitrogen and sediment of claycontribute to the water environment condition as eutrophic status.Keywords : Aquatic Productivity, Sediment, NO3, PO4, Tuntang River